Ways to improve the efficiency of the use of material and technical resources of medical institutions - Akhtayeva, S.; Tlessova, E.; Shokhan, R.; Akhmetova, S.S.; Shakeyev, S.S (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of the study is to analyze the material and technical resources of medical institutions and to develop the ways to improve the efficiency of their use. The objectives of the study are to develop the main directions and mechanisms for managing material and technical resources; to analyze the fixed assets of healthcare institutions; to assess the effectiveness of the material and technical resources management system. The state of the healthcare system today is one of the most important areas of social development of the state, but it does not meet the needs of the population. The issue of improving the development of the sphere is relevant. The article provides a review of the scientific literature on the topic of management and improvement of the use of material and technical resources of healthcare, analysis of the main indicators, namely the number of hospital organizations and the number of hospital beds, the main indicators of the condition and use of fixed assets in healthcare, the structure of fixed assets, SWOT analysis, etc. A regression analysis of the impact of health indicators on the change in gross domestic product was carried out. Correlation indicators are very high, which confirm the significance of the constructed model. Based on the above model, the forecast values of gross domestic product are calculated. And in the conclusion of the article, in order to improve the efficiency of the use of material resources, a mechanism for managing the material and technical resources of a medical institution is proposed. The mechanism of improving the use of material and technical resources consists of three stages, the use of which will lead to the effectiveness of their use. Methods: The following research methods are used in the work: historical, statistical, structural and functional, system and comparative analysis. Findings: The article considers and analyzes the use of fixed assets in healthcare institutions, the dynamics of the main indicators of the condition and use of fixed assets. Based on the analysis, strengths and weaknesses were identified, threats and opportunities of medical institutions were identified. In the age of digitalization, a special place is occupied by the material and technical base of medical institutions and their security, and therefore, for more efficient use of fixed assets, a mechanism for managing the material and technical resources of a medical institution is proposed. Conclusions: The work emphasizes the need to provide material and technical resources, since the Concept of Healthcare development focuses on the development of digital healthcare, and in order to implement the program, a very good material base is needed. In this regard, in our opinion, the above mechanism for managing the material and technical resources of medical institutions will lead to optimization and efficiency of their use, improving the quality and efficiency of services provided.